2004
DOI: 10.1093/jn/134.8.1887
|View full text |Cite
|
Sign up to set email alerts
|

Lutein Bioavailability Is Higher from Lutein-Enriched Eggs than from Supplements and Spinach in Men

Abstract: Lutein may be protective against diseases such as age-related macular degeneration (ARMD). At present, data regarding bioavailability of lutein from various sources are insufficient. Healthy men (n = 10) participated in an intervention study with a crossover design. After a 2-wk washout period during which they consumed a low-carotenoid diet, the men were administered 1 of 4 lutein doses (lutein supplement, lutein ester supplement, spinach, and lutein-enriched egg) for 9 d. All lutein doses provided 6 mg lutei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
3
13

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(225 citation statements)
references
References 49 publications
9
200
3
13
Order By: Relevance
“…Studies carried out to investigate differences in bioavailability between pure and esterified lutein do not support this hypothesis. One study reported no significant difference in serum lutein response between 6 mg lutein from spinach, 6 mg pure lutein and 10.23 mg lutein esters (Chung et al, 2004). In another study, serum response was greater from lutein esters than pure lutein (Bowen et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies carried out to investigate differences in bioavailability between pure and esterified lutein do not support this hypothesis. One study reported no significant difference in serum lutein response between 6 mg lutein from spinach, 6 mg pure lutein and 10.23 mg lutein esters (Chung et al, 2004). In another study, serum response was greater from lutein esters than pure lutein (Bowen et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…The efficacy of this hydrolysis of lutein esters into lutein occurs with an efficacy that is well below 5% (Breithaupt et al, 2002;Granado et al, 2002). Furthermore, a negative correlation between age and serum lutein levels in individuals consuming lutein esters has been reported that was not found in people supplementing with lutein (Chung et al, 2004). This may suggest that the ability to hydrolyse lutein esters declines with age.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic effects of choline availability during prenatal and postnatal development are just beginning to be investigated (51,52) . Eggs also provide highly bioavailable forms of the xanthophylls lutein and zeaxanthin, which are related to lower risks for age-related macular degeneration and cataracts (53)(54)(55)(56) as well as some types of cancer (57)(58)(59) and carotid artery atherosclerosis (60) . Eggs also provide satiety in the diet (61) and can be a valuable addition to a low-energy weight-loss diet (62) .…”
Section: Do No Harmmentioning
confidence: 99%
“…We are very familiar with this method, as we have used it in several of our recently published studies. [3][4][5][6] In our review article, we point out the limitations of the standard 'two-step method' commonly used by many laboratories to quantify MZ. These limitations include the following: its labour intensive nature due to manual collection; operator dependency and potential for human error; and a very long sample run time, rendering it difficult to perform bulk analysis (eg, for clinical trials).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…This claim is not correct. If saponification was not performed, carotenoid esters still would be detected using the method employed by Rasmussen et al, 3 as indicated by Chung et al 6 The esters elute after the free L and Z and during the period of detection. In the paper by Maoka et al 2 , the significance of the tested foods as dietary sources of MZ cannot be determined because they did not determine the absolute amount of MZ.…”
mentioning
confidence: 99%